Ureteroarterial Fistula: A Diagnosis Which Is Not Always Black and White - A. Haffar; T. Trump; A. A. Elbakry; K. McCluskey; M. W. Salkini; A. Luchey (Case Reports in Urology)
Ureteroiliac artery fistulas are a rare, life-threatening condition that requires a high index of suspicion for prompt diagnosis. Presurgical diagnosis is challenging as this condition can lie hidden despite advanced imaging modalities. We present two cases of patients presenting with gross hematuria and exsanguination in the setting of a ureteroiliac artery fistula. These cases highlight the difficulties in timely diagnosis and treatment in a multidisciplinary team.